The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/978-3-319-56932-1_26
|View full text |Cite
|
Sign up to set email alerts
|

Code-Based Cryptosystems Using Generalized Concatenated Codes

Abstract: The security of public-key cryptosystems is mostly based on number theoretic problems like factorization and the discrete logarithm. There exists an algorithm which solves these problems in polynomial time using a quantum computer. Hence, these cryptosystems will be broken as soon as quantum computers emerge. Code-based cryptography is an alternative which resists quantum computers since its security is based on an NP-complete problem, namely decoding of random linear codes. The McEliece cryptosystem is the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Goppa codes are still considered to be secure, as no structural attacks on these codes were found. On the other hand, the proposed GC code construction has no complete security analysis against structural attacks, such as the attacks proposed in [21,26,33]. This security analysis is subject to future work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goppa codes are still considered to be secure, as no structural attacks on these codes were found. On the other hand, the proposed GC code construction has no complete security analysis against structural attacks, such as the attacks proposed in [21,26,33]. This security analysis is subject to future work.…”
Section: Discussionmentioning
confidence: 99%
“…In [26], it was shown that generalized concatenated codes may withstand the aforementioned structural attacks. Furthermore, those codes enable higher code rates.…”
Section: Generalized Concatenated (Gc) Codes Over Gaussian and Eisens...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interleaved Goppa [94] GRS Ordinary concatenated [197] [198] Generalized concatenated [182] Table 18: Proposals for the McEliece Framework…”
Section: Code Proposed In Attackmentioning
confidence: 99%
“…In [26], a generalized concatenated (GC) code construction with inner OMEC codes over Gaussian integers and outer RS codes was proposed for the one-Mannheim error channel. GC codes are more robust against the structural attack from [25] than ordinary concatenated codes [27].…”
Section: Introductionmentioning
confidence: 99%